Psychometric Characteristics of the Chinese Version of the Tuberculosis Related-Stigma Scale in a Population of Medical Students and Its Correlation with Selected Demographic Characteristics - Yi Y; Sun M; Lu J; Dou X; Yu Y; Zhou L (Dove Medical Press, 2024)
Yaohui Yi, Meng Sun, Jiachen Lu, Xiaofeng Dou, Yingying Yu, Ling Zhou School of Public Health, Dalian Medical University, Dalian City, Liaoning Province, People's Republic of ChinaCorrespondence: Ling Zhou, School of Public Health, Dalian Medical University, Dalian City, Liaoning Province, People's Republic of China, Tel +86-411-8611-0368, Email zhouling0609@163.comBackground: As future health workers, medical students' attitudes towards tuberculosis (TB) patients can impact TB control. However, in China, there is a lack of well-quantified assessment regarding the stigma among medical students towards TB patients. Therefore, this study aimed to validate the Chinese version of the Tuberculosis related-Stigma Scale (TSS) in medical students and to apply the scale to measure stigma and its determinants.Methods: A total of 1035 eligible medical students participated in the cross-sectional questionnaire. Exploratory factor analyses (EFA) and confirmatory factor analyses (CFA) were first conducted to test Chinese version of the TSS construct validity, and then internal consistency was assessed using Cronbach's α. Finally, multiple linear regression analyses were conducted to identify predictors of stigma.Results: EFA extracted two factors ("Social distance" and "Exclusionary sentiments"). The CFA further confirmed the two-factor construct. The internal consistency, convergent and divergent validity of the adapted Chinese version of the TSS was acceptable. Furthermore, Whether one has received TB health education and whether know a person with TB are associated with all dimensions of TB stigma, while differences in sex and place of residence play different roles in influencing the different dimensions of stigma.Conclusion: The adapted Chinese version of the TSS can be used to assess the level of stigma among medical students in China towards tuberculosis patients. When implementing future interventions to reduce stigma associated with TB, special attention should be given to medical students from urban areas, of male gender, who have not received TB health education, and no know a person with TB. However, these two dimensions ("Social distance" and "Exclusionary sentiments") are impacted by different determinants and should therefore be addressed separately when designing, implementing, and evaluating measures to reduce stigma.Keywords: tuberculosis related-stigma scale, medical student, psychometrics, determinants